2017
DOI: 10.7205/milmed-d-16-00121
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Insights on Surgical Activity in a New Modern Warfare: The French Role 2 in Bangui, Central African Republic

Abstract: Our study demonstrated original and dynamic insights into the nature of surgical activity throughout the operation with mainly orthopedic surgery during the initial deployment for management of combat casualties and general surgery later, dedicated to elective surgery for local citizens. These data should enhance staffing, training, and deployment of future surgical teams in combat settings with continuous training programs to maintain specific competences, especially in cases of low surgical activity, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We found an average age of 28.9 years, with a male predominance of 98%. This mean age is close to that of Barbier et al [6] who found an average age of 29, with a male predominance of 86%. The exposed population is essentially made up of young men.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found an average age of 28.9 years, with a male predominance of 98%. This mean age is close to that of Barbier et al [6] who found an average age of 29, with a male predominance of 86%. The exposed population is essentially made up of young men.…”
Section: Discussionsupporting
confidence: 90%
“…In our series, 74.5% of patients were military personnel. Barbier et al had also found in their study 60% military patients [6]. Coulibaly et al in Côte d'Ivoire observed a predominance of civilians (68.6%) [7].…”
Section: Discussionmentioning
confidence: 76%
“…Since 2003, the French Military Health Service (Service de Santé des Armées) [7] has managed an electronic database that contains a prospective surgical record of procedures performed by deployed surgeons at Role 2 (Forward Surgical Teams that provide primary care and basic emergency treatment) and Role 3 (Combat Support Hospitals that provide the highest level of medical care in combat zones) levels. This registry was the source of several studies that focused on the surgical workload of French MTFs (e.g., Bonnet et al, 2012 [5]; Barbier et al, 2014 [3]; Malgras et al, 2016 [8]; de Lesquen et al, 2016 [9]; Beranger et al, 2017 [10]; Barbier et al, 2017 [11]).…”
Section: Introductionmentioning
confidence: 99%
“… Military Surgical Mission 1 article -Does not include education -Post-op follow-up and outcomes applicable -Does not include post-op follow-up or outcomes -Does not assess the attitudes of the local population Surgery outreach performed by foreign military personnel in a country in SSA for a defined period. Must include operations on local civilians in addition to war-related surgeries [ 72 ]. 22-month mission.…”
Section: Resultsmentioning
confidence: 99%